Quiron: Historical Fiction Podcast.: Reflections on Ficstoria as a research-creation methodology in performing arts. (The Voz a Vos Bulletin, 2022)
This paper attempts to do a practical and theoretical reflection on the concept "Ficstoria" (Fiction with History basis) as a research/creation methodology in the performing arts. It will address the four pillar components of this methodology: Research, creation, criticism, and pedagogy. A particular emphasis will be placed on research to reveal the tense relationship between History and Dramatic Fiction. This entire reflection is based on the experience of research and creation that put together "Quirón", a historical fiction podcast series developed by the directing student Camilo Castro Hormaza as his Major thesis. The thesis presented to the ASAB Faculty of Arts UDFJC obtained summa cum laude recognition.